Group Size and Incentives to Contribute: A Natural Experiment at Chinese Wikipedia - Zhang, Xiaoquan (Michael); Zhu, Feng (American Economic Review, 2011)
The literature on the private provision of public goods suggests an inverse relationship between incentives to contribute and group size. We find, however, that after an exogenous reduction of group size at Chinese Wikipedia, the nonblocked contributors decrease their contributions by 42.8 percent on average. We attribute the cause to social effects: contributors receive social benefits that increase with both the amount of their contributions and group size, and the shrinking group size weakens these social benefits. Consistent with our explanation, we find that the more contributors value social benefits, the more they reduce their contributions after the block. (JEL H41, L17, L82)